2020
DOI: 10.3390/su122410397
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Trust and Commitment in Complex Project Networks through Dedicated Investment in Partnership Management

Abstract: An absence of trust among partners can magnify the risk in a complex project by increasing behavioural uncertainty. Partnership trust can effectively substitute for control, reducing variability of outcomes and increasing value-adding strategic collaboration. It is introduced as strategic countermeasures against risks associated with project complexity that can only be achieved with commitment from all partners. This research conceptualises partnership trust on four dimensions and investigates the roles of ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 124 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…At the outset, some researchers believed that the partnerships had a positive effect on firm performance [3,39], while some suggested that the effect could be negative [2], and yet others argued that the two are unrelated [6]. To resolve these inconsistencies, scholars conducted in-depth investigations using dimensional analysis [27,44], comparisons of different types of firms [45] or modes of cooperation [46,47], or dynamic analysis of different development stages [6], with a variety of research methodologies [48] to examine the paths and boundaries between strategic partnership and firm performance [14,18,[49][50][51] (Table 2).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…At the outset, some researchers believed that the partnerships had a positive effect on firm performance [3,39], while some suggested that the effect could be negative [2], and yet others argued that the two are unrelated [6]. To resolve these inconsistencies, scholars conducted in-depth investigations using dimensional analysis [27,44], comparisons of different types of firms [45] or modes of cooperation [46,47], or dynamic analysis of different development stages [6], with a variety of research methodologies [48] to examine the paths and boundaries between strategic partnership and firm performance [14,18,[49][50][51] (Table 2).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of this study indicate that, as a result of an imperfect entrepreneurial environment, firms in developing countries with Eastern cultural heritage face both productivity and transaction constraints during value creation and capture processes, respectively. As a result, many firms choose to form strategic partnerships to strengthen interfirm trust, commitment, reciprocity, and rights through close collaboration [27], thereby bridging the value chain gap, lowering transaction costs, and increasing productivity to some extent.…”
Section: Research Findingmentioning
confidence: 99%
See 1 more Smart Citation
“…The result indicates a significant and positive relationship between digital technologies implementation (DTI) and supply chain collaboration (SCC) which supports H4 (β = 0.85; P < 0.05). The result resonates with various studies as follows: According to Shin et al ., 2020, the foundation of effective supply chain operations, whether or whether they use technologies, is the process of developing relationships among and between supply chain participants.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…The analysis of the relationship between the behavioral risks of stakeholders is insufficient. Meanwhile, due to the mutual influence of behaviors among stakeholders, some scholars further study the synergy and partnership among stakeholders in project construction [28][29][30][31]. However, behavioral risk relationships are not integrated into the risk network to analyze the impact of overall relationships on the construction of engineering projects.…”
Section: Literature Review 21 Project Risk Managementmentioning
confidence: 99%